ARCADES: analysis of risk from cyberattack against defensive strategies for the power grid. Issue 3 (31st May 2018) - Touhiduzzaman, Md; Hahn, Adam; Srivastava, Anurag
Abstract : In this study, the authors introduce ARCADES (Analysis of Risk from Cyberattack against DEfensive Strategy), a technique to systematically explore the cybersecurity defence strategies based on contingency rankings in power systems. While cybersecurity defensive standards exist, these approaches are primarily based on expert opinions, rather than systematic studies of risk. ARCADES presents an approach to identify improved cybersecurity defensive strategies based on a graph‐based cyber‐physical security model that is evaluated by resistance‐distance metrics and then prioritised based on contingency analysis studies of the system. This study also proposed a technique that identifies the most critical cybersecurity mechanisms to protect the power grid. Planning and operation: those two applications for cybersecurity on power grid mainly explored in this study. For planning, a systematic method is developed to verify the effectiveness of security strategies and for operation, prioritised the security mechanism for auditing and monitoring purpose. As a case study, they analyse the IEEE‐14 bus, IEEE‐30 bus, and IEEE‐118 bus systems, observe the defensive strategies, and calculate substation criticality ranking by using the authors' proposed method.